2005
DOI: 10.1074/jbc.m505910200
|View full text |Cite
|
Sign up to set email alerts
|

Similar Patterns of Mitochondrial Vulnerability and Rescue Induced by Genetic Modification of α-Synuclein, Parkin, and DJ-1 in Caenorhabditis elegans

Abstract: How genetic and environmental factors interact in Parkinson disease is poorly understood. We have now compared the patterns of vulnerability and rescue of Caenorhabditis elegans with genetic modifications of three different genetic factors implicated in Parkinson disease (PD). We observed that expressing ␣-synuclein, deleting parkin (K08E3.7), or knocking down DJ-1 (B0432.2) or parkin produces similar patterns of pharmacological vulnerability and rescue. C. elegans lines with these genetic changes were more vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
190
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(197 citation statements)
references
References 66 publications
5
190
1
1
Order By: Relevance
“…MPP þ , rotenone and PQ have all been shown to alter Parkin solubility, which facilitates its aggregation, decreases proteasome activity and causes cell injury and death. 53 In contrast, in the C. elegans controlled genetic background, the sensitivity model proposed by Ved et al 44 has shown that PQ toxicity is not enhanced by the Parkinson-linked genetic modifications, at variance with chemicals exerting an effect specifically on mitochondrial complex I.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…MPP þ , rotenone and PQ have all been shown to alter Parkin solubility, which facilitates its aggregation, decreases proteasome activity and causes cell injury and death. 53 In contrast, in the C. elegans controlled genetic background, the sensitivity model proposed by Ved et al 44 has shown that PQ toxicity is not enhanced by the Parkinson-linked genetic modifications, at variance with chemicals exerting an effect specifically on mitochondrial complex I.…”
Section: Figurementioning
confidence: 99%
“…39 A major difference in the interaction with cellular proteins between PQ and complex I acting chemicals is also highlighted in a study carried out in C. elegans, in which the patterns of vulnerability and rescue have been compared after genetic manipulation. 44 Ved et al 44 created a susceptibility model in C. elegans by overexpressing a-synuclein (which is normally not expressed in the worm) and deleting Parkin or knocking down DJ-1. C. elegans lines with these transgenic traits were more vulnerable than non-transgenic worms to mitochondrial complex I inhibitors including Rotenone.…”
Section: Pq Toxicity In Animal Models and The Underlying Mechanismsmentioning
confidence: 99%
“…The link between parkin function and mitochondrial performance was further strengthened by data from an unbiased proteomic approach that showed alterations in mitochondrial function in the ventral midbrain of parkin-null mice and revealed systemic changes due to oxidative stress (15). Recent data using Caenorhabditis elegans devoid of parkin have reinforced the importance of this protein to mitochondrial function (16).…”
mentioning
confidence: 96%
“…Rare familial forms of parkinsonism transmitted in autosomal dominant or recessive patterns have been traced to mutations in multiple genes. For some of these autosomal forms of parkinsonism, mitochondrial dysfunction is emerging as a common theme of pathogenesis (Ved et al, 2005).…”
Section: Introductionmentioning
confidence: 99%